Optimizing the Ability of Fifth Grade Elementary School Teachers in Preparing Character-Based LKPD Through in House Training - Srihartati, Nanik; Wati, Unik Ambar (MIMBAR PGSD Undiksha, 2024)
Student Worksheets (LKPD) are one of the tools that can assist students in the learning process. LKPD must be prepared in accordance with the applicable curriculum. Therefore, the development of character-based LKPD is an important aspect that needs attention. This research aims to analyze the improvement of the ability to develop character-based LKPD through in-house training. The study employs the School Action Research (SAR) approach, adopting the Mc. Taggart model. The research is conducted in two cycles, each consisting of two meetings. Each cycle includes four stages: planning, action, observation, and reflection. The participants in the study are all fifth-grade teachers in the Dabim 2 Jatinom District, totaling 19 participants. Data are collected through observation methods and assessments of LKPD produced by the participants during the research process. The results of the research indicate that In-House Training effectively enhances teachers' ability to develop character-based LKPD. There is a significant improvement in all evaluation aspects, including material, language, presentation, and graphics. Overall, there is an increase in the average success rate from 60% in the first cycle to 84.21% in the second cycle. As a recommendation, this study suggests the continuation of In-House Training and the adoption of more in-depth character-based teaching methods for the professional development of teachers.